Improving Public Service Delivery through E-Government Innovation in Regional Bureaucracy: A Case Study of Disdukcapil Sleman - Sa’adih, Sa’adih; Fahmi, Ade; Perdanaputra, Decky (JURNAL SOSIAL DAN HUMANIS SAINS, 2021)
This study analyzes the implementation of e-Government in improving the quality of public services at the Department of Population and Civil Registration (Disdukcapil) in Sleman Regency. Utilizing qualitative descriptive methods with data collected through interviews, documentation, and literature studies prior to 2021, the research finds that innovations such as the "SILAKAS" (Sistem Layanan Kependudukan Sleman) and "PANDAWA" (Pelayanan Administrasi Kependudukan via WhatsApp) applications have improved service accessibility, efficiency, and transparency. Despite some technical and infrastructural constraints, the results indicate significant strides toward bureaucratic reform and digital-based service excellence. The study contributes to the discourse on local public administration reforms and the role of digitalization in regional governance.